ANALISIS PENGARUH BUDAYA DAN PERENCANAAN STRATEGIS TERHADAP KINERJA PERUSAHAAN - `Mashur Razak (AkMen JURNAL ILMIAH, 2009)
The objectives of the study are to measure and analyze the influence of the strategic planning and culture on the performance of company. The study indicates that the strategic environment has a positive but insignificant influence on the strategic planning of the company. However, the strategic environment has a positive and significant influence on the performance of the company in the region. The strategic environment therefore has a positive but insignificant influence on the company performance through strategic planning. Culture has a positive and significant influence on both the strategic planning and the performance of the company. Therefore, culture has a direct as well as indirect influence on the performance of the company in through strategic planning.